Effects of restoration of the euthyroid state on epicardial adipose tissue and carotid intima media thickness in subclinical hypothyroid patients - ÖZBEN SADIÇ, BESTE; YAVUZ, DİLEK; ÜSTAY, ÖZLEM (HUMANA PRESS INC, 2015)
Epicardial adipose tissue (EAT) thickness is a novel cardiovascular risk indicator, whereas carotid intima media thickness (CIMT) is a known marker of subclinical atherosclerosis. The aim of this study was to measure EAT thickness and CIMT in subclinical hypothyroid (SCH) patients and to determine the effect of restoration of the euthyroid state on these variables. The study included 43 patients with SCH (mean age: 35.2 +/- 10.7 years; F-M ratio: 42: 1) and 30 healthy controls (mean age: 34.5 +/- 8.2 years; F-M ratio: 25: 5). EAT thickness and CIMT were measured via conventional echocardiography and ultrasonography. Among the patients, 23 were followed up with L-thyroxine replacement until restoration of the euthyroid state and re-evaluated 6 months after baseline. Basal EAT thickness was higher in the SCH patients than in the controls (3.2 +/- 0.7 vs. 2.3 +/- 0.3 mm-p < 0.0001), whereas CIMT was similar in both groups (0.50 +/- 0.09 vs. 0.48 +/- 0.04 mm). EAT thickness was correlated with CIMT in the patient group (r = 0.39, p = 0.01), but this correlation was not evident based on multivariate analysis when corrected for age and body mass index (r(2) = 0.47 and p = 0.0001 for the model). In the follow-up patient subgroup, both EAT thickness and CIMT decreased significantly following L-thyroxine treatment, when normal TSH levels were attained (3.4 +/- 0.7 vs. 2.3 +/- 0.5 mm-p = 0.007 and 0.51 +/- 0.09 vs. 0.46 +/- 0.07 mm-p = 0.01, respectively). EAT thickness was greater in the SCH patients than in controls, whereas CIMT was similar in both groups. Restoration of the euthyroid state with L-thyroxine treatment was associated with significant decreases in EAT thickness and CIMT in the group of patients that received L-thyroxine treatment and, as such, might reduce the cardiovascular risk associated with SCH.
Keywords: Epicardial adipose tissue thickness; Carotid intima media thickness; Subclinical hypothyroidism; CORONARY-ARTERY-DISEASE; VASCULAR SMOOTH-MUSCLE; METABOLIC SYNDROME; THYROID-FUNCTION; RISK-FACTOR; INDEPENDENT PREDICTOR; CLINICAL-SIGNIFICANCE; CARDIOVASCULAR RISK; FREE-THYROXINE; HEART-DISEASE